Magnetic resonance imaging findings in acute febrile encephalopathy in children - Hirekerur, Vikram L.; Gaikwad, Shahaji Y.; Kolewad, Aparna B. (International Journal of Contemporary Pediatrics, 2024)
Background: This prospective observational study aims to study magnetic resonance imaging (MRI) findings in the setting of acute febrile encephalopathy in children between 1 month to 18 year of age group. Methods: This study was conducted in patients of acute febrile encephalopathy admitted in pediatric intensive care unit (PICU) at tertiary care centre during January 2019 to December 2019 in age group one month to 18 years. 32 patients satisfied the inclusion criteria. Results: Of the 32 patients included in the study MRI was done in 28 patients. MRI brain was normal in 17 patients and abnormalities were found in 11 patients. Majority findings were cerebral enema and restricted diffusion 3 (10.5%). Other findings were T2 hyperintensity and FLAIR hyperintensity lesion in basal ganglia and thalami region 2 (7%), T2 and FLAIR hyperintensity hippocampal lesion in hippocampus 2 (7%), haemorrhagic lesion 1 (3.5%). Conclusions: Acute febrile encephalopathy is a life-threatening condition. It is important to identify the possible aetiology for directing specific treatment. Amongst others MRI is one modality that has the potential to identify possible aetiology. Paediatric intensive care physicians are not always updated regarding utility of MRI and its findings in acute febrile encephalopathy. The main reason being non-inclusion of this subject in curriculum. This study was intended to understand all the possible MRI findings in acute febrile encephalopathy, correlate it with clinical findings and ultimately aid in management of these cases.